Aplicación de satélite SAR, mediante el método Cloude Pottier para la clasificación de suelos. - Huayanay Villar, José Luis (2024)
This research whose purpose is to apply the Cloude_Pottier polarimetry method in a Synthetic Aperture Radar (SAR) image, Sentinel 1, for the classification of soils with Sentinel-1 radar images in Band C and which belongs to the European Space Agency (ESA). The methods and techniques that were applied to each radar image consisted of classifying the angle of incidence, intensity, backscatter or others for each area under study. The classification method was used as: H-Alpha, in the Cloude-Pottier method. Some simulation algorithms were also used to correlate and characterize wetlands as water, lagoons, vegetables or others. The classification results in the polarimetric entropy parameter and polarimetric alpha parameter, which are the randomness of the data in a radar image and the dispersion mechanisms of radar waves in a Sentinel-1 image respectively. This method allows efficient classification and allows forecasts to be made over time. Likewise, the nine classes have certain characteristics according to the area of ​​study.